2014
DOI: 10.3354/dao02689
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous nodules in Irrawaddy dolphins: an emerging disease in vulnerable populations

Abstract: The presence of cutaneous nodules is reported in vulnerable populations of Irrawaddy dolphins Orcaella brevirostris from Malaysia (Kuching, Bintulu-Similajau, KinabatanganSegama and Penang Island), India (Chilika Lagoon) and Bangladesh (Sundarbans). Approximately 5700 images taken for photo-identification studies in 2004 to 2013 were examined for skin disorders. Nodules were detected in 6 populations. They appeared as circumscribed elevations of the skin and varied in size from 2 to > 30 mm, were sparse or num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…In the present study, the encounter rates of humpback dolphins seem to have declined between 2013 and 2016, which may indicate either decreasing relative abundance or geographic shifts in the occurrence of this species. Cutaneous nodules, an emerging skin disease, have been observed in Irrawaddy dolphins in Matang (Ponnampalam, Kuit, & Chong, ), similar to observations reported by Van Bressem et al (). The presence of skin diseases suggests that the coastal cetaceans of Matang may be living in a compromised environment that is exposed to sewage and organic pollution (Van Bressem et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the encounter rates of humpback dolphins seem to have declined between 2013 and 2016, which may indicate either decreasing relative abundance or geographic shifts in the occurrence of this species. Cutaneous nodules, an emerging skin disease, have been observed in Irrawaddy dolphins in Matang (Ponnampalam, Kuit, & Chong, ), similar to observations reported by Van Bressem et al (). The presence of skin diseases suggests that the coastal cetaceans of Matang may be living in a compromised environment that is exposed to sewage and organic pollution (Van Bressem et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The symptoms caused by S. iniae infection can be variable in different host species. Previous studies have shown that S. iniae infection could cause multifocal cutaneous abscesses in dolphins (Van Bressem, Minton, Sutaria, Kelkar, Peter & Zulkarnaen ) and bacteraemic cellulitis in humans (Sun, Yan, Yeh, Lee & Lu ). In fish, the disease caused by infection with S. iniae generally results in a septicaemia, meningitis and panophthalmitis, and results in high levels of morbidity and mortality (Agnew & Barnes ).…”
Section: Discussionmentioning
confidence: 99%
“…raised, grey, orange or reddish, sometimes ulcerated, skin lumps (Van Bressem et al, 2009c). Cutaneous nodules unrelated to lobomycosis were reported in free-ranging Indo-Pacific bottlenose dolphins Tursiops aduncus from Japan, in Irrawaddy dolphins Orcaella brevirostris from Malaysia, India and Bangladesh, and in common minke whales Balaenoptera acutorostrata and a white-beaked dolphin Lagenorhynchus albirostris from Icelandic waters (Bertulli et al, 2012;Van Bressem et al, 2013;2014). Though likely infectious their aetiology is still unknown.…”
Section: Discussionmentioning
confidence: 99%